2012
DOI: 10.3748/wjg.v18.i40.5709
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl pyruvate protects against experimental acute-on-chronic liver failure in rats

Abstract: AIM:To investigate the protective effects of ethyl pyruvate (EP) on acute-on-chronic liver failure (ACLF) in rats.METHODS: An ACLF model was established in rats, and animals were randomly divided into normal, model and EP treatment groups. The rats in EP treatment group received EP (40 mg/kg) at 3 h, 6 h, 12 h and 24 h after induction of ACLF. Serum endotoxin, high mobility group box-1 (HMGB1), alanine transaminase (ALT), tumor necrosis factor-α (TNF-α), interferon-α (IFN-γ), interleukin (IL)-10 and IL-18 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…[16][17][18][19] However, the role of TSA on the ALF is still unknown. In this study, we observed how TSA affected on ALF rats' digestive system, including the liver, the small intestine, and the colon and further explored its potential mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] However, the role of TSA on the ALF is still unknown. In this study, we observed how TSA affected on ALF rats' digestive system, including the liver, the small intestine, and the colon and further explored its potential mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced acute fatal liver injury is the leading cause of acute liver failure (ALF) in the developed countries [4346], and ALF has a high mortality and the treatment is still quite challenging [43]. …”
Section: Ep Ameliorates Severe Acute Pancreatitis (Sap) and Attenuatementioning
confidence: 99%
“…Acute-on-Chronic liver failure (ACLF) rats have significantly increased serum endotoxin, TNF-α, HMGB1, IFN-gamma and IL-18, EP administration (40 mg/kg was intraperitoneally injected at 3 h, 6 h, 12 h, 24 h after the induction of ACLF, and samples were taken 48 h after the induction of ACLF) decreases all of these changes to protect against ACLF in rats [46]. …”
Section: Ep Ameliorates Severe Acute Pancreatitis (Sap) and Attenuatementioning
confidence: 99%
“…The potent antioxidant effects of EP have been shown in some studies [14]. EP is basically derived from pyruvic acid [15]. It has also been shown that this molecule improves organ dysfunction in some situations, such as sepsis [16], ileus [17], acute pancreatitis [18] and organ ischemia and hemorrhagic shock [19,20,21].…”
Section: Introductionmentioning
confidence: 99%